Zum Gedenken an Gerhard Fezer (1938-2014). Reden der Akademischen Gedenkfeier der Fakultät für Rechtswissenschaft am 30. Oktober 2015 - Repgen, Tilman (Hamburger Universitätsreden Neue Folge, 2016)
This publication documents the speeches held at the Academic Commemorative Ceremony of Gerhard Fezer (1938-2014) at the University of Hamburg on October 30th, 2015. Supplemented by greetings of the Dean of the Faculty of Law, the five speeches, each with a different accent, convey an impressive picture of the colleagues and academic teachers who died at the age of 75 on August 15th, 2014. Gerhard Fezer had taken up a professorship for criminal law and criminal procedural law in Hamburg in 1978 and emerged as a professor in 2004 (but continued teaching); he was a member of the University of Hamburg for almost thirty years.